Influence of sex, season and environmental air quality on experimental human pneumococcal carriage acquisition: a retrospective cohort analysis. Issue 2 (11th April 2022) - Cheliotis, Katerina S.; Jewell, Christopher P.; Solórzano, Carla; Urban, Britta; Collins, Andrea M.; Mitsi, Elena; Pojar, Sherin; Nikolaou, Elissavet; German, Esther L.; Reiné, Jesús; Gordon, Stephen B.; Jochems, Simon P.; et al.
Streptococcus pneumoniae (pneumococcus) is the most commonly identified bacterial cause of pneumonia and the leading infectious cause of death in children under 5 years of age worldwide. Pneumococcal disease follows a seasonal pattern with increased incidence during winter. Pneumonia burden is also associated with poor air quality. Nasopharyngeal carriage of the bacterium is a pre-requisite of invasive disease. We aimed to determine if susceptibility to nasopharyngeal pneumococcal carriage varied by season and which environmental factors might explain such variation. We also evaluated the influence of sex on susceptibility of carriage. We collated data from five studies in which human volunteers underwent intranasal pneumococcal challenge. Generalised linear mixed-effects models were used to identify factors associated with altered risk of carriage acquisition, specifically climate and air-quality data. During 2011–2017, 374 healthy adults were challenged with type 6B pneumococcus. Odds of carriage were significantly lower in males (OR, 0.61; 95% CI, 0.40–0.92; p=0.02), and higher with cooler temperatures (OR, 0.79; 95% CI, 0.63–0.99; p=0.04). Likelihood of carriage was also associated with lower concentrations of local fine particulate matter concentrations (PM2.5 ) and increased local rainfall. In contrast to epidemiological series, experimental challenge allowed us to test propensity to acquisition during controlled exposures; immunological explanations for sex and climatic differences should be sought. Using a controlled human model of infection, this study correlated propensity of pneumococcal colonisation with environmental and climatic factors; likelihood of colonisation is significantly lower in males than females, and inversely correlated with PM2.5 https://bit.ly/3MERdjz